2020
DOI: 10.3233/jad-190830
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk and Cognitive Function in Middle-Aged and Older Hispanics/Latinos: Results from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: Background: Cardiovascular disease is linked to cognitive decline and disorders (e.g., dementia). The evidence is based largely on older non-Latino White cohorts. Objective: Examine the association between global vascular risk and cognitive function among Hispanics/Latinos in the United States. Methods: We used data from a large sample of stroke-and cardiovascular disease-free, middle-aged and older Hispanics/Latinos with diverse backgrounds (n = 7,650) from the Hispanic Community Health Study/Study of Latinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 46 publications
7
32
0
Order By: Relevance
“…This is consistent with previous studies which reported that post-stroke dementia is more prevalent in men [35]. In large-scale populationbased cohort studies on the association of cardiovascular risk [36] and blood pressure pattern [37] with cognitive function, researchers have consistently reported that mid-life vascular disease has a more substantial effect on dementia onset. Our ndings highlight the importance of midlife as a critical period for later cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies which reported that post-stroke dementia is more prevalent in men [35]. In large-scale populationbased cohort studies on the association of cardiovascular risk [36] and blood pressure pattern [37] with cognitive function, researchers have consistently reported that mid-life vascular disease has a more substantial effect on dementia onset. Our ndings highlight the importance of midlife as a critical period for later cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies which reported that post-stroke dementia is more prevalent in men [50]. In large-scale populationbased cohort studies on the association of cardiovascular risk [51] and blood pressure pattern [52] with cognitive function, researchers have consistently reported that mid-life vascular disease has a more substantial effect on dementia onset. Our ndings highlight the importance of midlife as a critical period for later cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies which reported that post-stroke dementia is more prevalent in men [ 35 ]. In large-scale population-based cohort studies on the association of cardiovascular risk [ 36 ] and blood pressure pattern [ 37 ] with cognitive function, researchers have consistently reported that mid-life vascular disease has a more substantial effect on dementia onset. Our findings highlight the importance of midlife as a critical period for later cognitive function.…”
Section: Discussionmentioning
confidence: 99%